Mediating effect of frailty on social isolation and cognitive function among the elderly - JIANG Meiting，YANG Wenfei，ZHANG Xiang，CAI Xin，GUAN Aijun，ZENG Dongyang (预防医学)
Objective:To examine the mediating effect of frailty on social isolation and cognitive function among the elderly. Methods:Demographic information, smoking, alcohol consumption and cognitive function of the elderly at ages of 60 years and older were collected from the China Health and Retirement Longitudinal Study 2020. Social isolation and frailty were evaluated using social isolation index and frailty index, respectively. The mediating effect of frailty on social isolation and cognitive function was analyzed using the Process program, and the significance of the mediating role was tested using the Bootstrap test. Results:A total of 2 822 individuals were enrolled, including 1 483 males (52.55%) and 1 339 females (47.45%). There were 2 497 (88.48%) and 325 (11.52%) individuals at ages of 60-<75 years and ≥75 years, respectively. The median cognitive function score was 14 (interquartile range, 16) points. There were 432 cases with social isolation (15.31%), with a median social isolation index of 10 (interquartile range, 5) points. The median frailty index was 0.11 (interquartile range, 0.15). There were 1 111 individuals without frailty, accounting for 39.37%; 1 214 individuals with pre-frailty, accounting for 43.02%; and 497 individuals with frailty, accounting for 17.61%. Mediating effect analysis showed that social isolation affected cognitive function directly and negatively with the effect value of -0.773 (95%CI: -0.899 to -0.647), and also affected cognitive function by frailty indirectly and negatively with the effect value of -0.147 (95%CI: -0.188 to -0.110), with the mediating effect contributed 15.98% of the total effect. Conclusion:Frailty can directly or indirectly affect cognitive function among elderly through social isolation.